Toilet Soap Formulation and Additives for Its Enhanced Physicochemical and Medicinal Properties - Abdul, Aminullah Zakariyyah; Karamat, Nazia; Tar, Usman Alhaji; Saka, Tahiru; ABUBAKAR, ABDULHALIM MUSA; Memon, Hafeez-ur-Rahman (University of Thi-Qar Journal of Science, 2024)
Human skin is an island in constant interaction between diverse microorganisms (Archaea, fungi, bacteria, and protozoa), especially the inner elbow, armpit and buttocks, of which an imminent health danger is possible during injury or their sustained proliferation. Fat-soluble lauric acid-containing palm kernel oil, hardness-giving caustic soda and water solvent were essential ingredients used to produce toilet soap in this study, via a mechanized setup. Free caustic alkali (FCA), pH and moisture content (MC), as determined for additive (honey, clove, black seed) formulations A, B, C, D and E, which are respectively in the range of 0.006-0.02%, 7.10-9.97, and 7.33-15.33%, gave a soap of desired medicinal functionality. Formulation E physicochemical property compares favorably with other soaps, including Septol, Dettol, Premier, Joy, Sunlight, and Premier Cool found in Nigerian markets. It is found that the three additives introduced into the formulation in the ratio of 33, 50 and 17%, respectively, are responsible for its septic, antioxidant, antimicrobial and sanitizing properties. With this fit achieved, improvement, packaging and mass production of the produced toilet soap already having satisfactory foam stability, lathering, cleansing, fragrance, form and quality (according to SNI standard), is encouraged in this part of the world.